Evaluasi Kualitas Lulusan S1 PJKR Di Wilayah Gresik, Sidoarjo & Mojokerto - Hamdani Hamdani; Setiyo Hartoto; Heryanto Nur Muhammad; Hari Wisnu; Sri Wicahyani (Jendela Olahraga, 2022)
The purpose of this study was to evaluated the quality graduates of S1 Physical Education in Recreational Health (PJKR) in Gresik, Sidoarjo and Mojokerto areas. The research method used is a survey with data collection techniques using a questionnaire. The subjects of this study were S1 graduates of Recreational Health Physical Education (PJKR), Faculty of Sports Science, States University of Surabaya. The sampling technique used was quota sampling. The sample in this study was 30 students who live in Gresik, Sidoarjo and Mojokerto areas. The results showed that the "Performance" indicator in "Medium" category, the "Time discipline" indicator in "Low" category, the "Consequent" indicator in "Medium" category, the "Professional" indicator in “Medium” category, the “Teamwork” indicator in “Medium” category, the “Loyalty” indicator in “Medium” category, the “Caring” indicator in “Low” category, the “Persistence” indicator in “Medium” category, the “Competent” indicator in “Medium” category and “IT Mastery” in “High” category. The conclusions of this study based on stakeholders assesment in general, graduates quality of Physical Education Health and Recreation (PJKR) there are two indicators that become a reflection to get special attention, namely increasing time discipline and caring.